Proximal vs. total gastrectomy for proximal advanced gastric cancer: a systematic review and meta-analysis of propensity score-matched studies - Liu, Chengcong; Li, Yanlei; Liang, Yan; Tian, Zhen; Zhang, Lin (Frontiers in Oncology, 2025)
BackgroundThe optimal surgical approach for locally advanced proximal gastric cancer (LAPGC) remains controversial. While total gastrectomy (TG) is widely accepted, proximal gastrectomy (PG) is increasingly considered to preserve function. This study represents the first meta-analysis to comprehensively compare the surgical and oncological outcomes of PG versus TG for LAPGC using data from propensity score-matched (PSM) studies, addressing a critical gap in surgical decision-making.MethodsA comprehensive search of various electronic databases was conducted. Studies comparing PG and TG in LAPGC with PSM methodology were included. Pooled hazard ratios (HRs), odds ratio (OR) and mean difference (MD) with 95% confidence intervals (CI) were calculated using a random-effects model. Primary outcomes were overall survival (OS) and disease-free survival (DFS). Secondary outcomes included surgical metrics and postoperative complications.ResultsA total of 265 articles were screened, and five retrospective studies were included in this meta-analysis, comprising 412 patients after PSM. Surgical approaches (OR 1.03, P = 0.896), positive surgical margins (OR 2.83, P = 0.08), and adjuvant chemotherapy rates (OR 1.07, P = 0.19) were similar between the PG and TG groups. PG resulted in significantly shorter operative times (MD 25.7, P<0.001) but higher blood loss (MD -21.65, P = 0.02) and fewer lymph nodes harvested (MD 6.23, P<0.001). Furthermore, the number of metastatic lymph nodes was similar between the two groups (MD 0.62, P = 0.07), with the exception of lymph node stations 5 and 6, where the metastatic rates in the TG group were 0.82% and 1.6% (P = 0.645), respectively. Postoperative complications were lower in the PG group, but the difference was not statistically significant (OR 1.24, P = 0.289). Hospital stay was significantly shorter in the PG group (MD 0.81, P = 0.001). No significant differences in the 5-year OS or RFS were found (HR 0.99, P = 0.48 for OS; HR 0.83, P = 0.87 for RFS). Sensitivity and publication bias analyses supported the robustness and consistency of the results.ConclusionFor selected patients with LAPGC, PG offers similar curative potential and oncological efficacy as TG, making it a safe option.